Pengaruh Penggunaan Media Kartu Kata Dalam Meningkatkan Kemampuan Membaca Bagi Siswa Kelas II A SDI Belang - Helena Susanti Dua Kuki; Yohenes Ehe Lawotan; Hermus Hero (Departement of Mathematics Education, 2023)
This study aims to determine the positive effect of using word card media in improving student learning outcomes in Indonesian language learning for class IIA SDI Belang students. This research is a quantitative research. The research method used was pre-experimental using one group pretest and posttest design. The sample in this study was 18 0 people. Data collection techniques in this study used tests, observation, and documentation. The results of this study classically show that the average pretest score is 63.9 and the average posttest score is 78.9. The data analysis technique used is simple statistical analysis with the help of the SPSS program. The results of the study showed sig = 0.000≤0.05, it was said that there was a significant difference between the results of the pre-test and post-test which indicated that the alternative hypothesis proposed by the researcher was accepted, namely that there was a significant positive influence on learning Indonesian reading material for class IIA SDI students Striped.